CapNet: A Wireless Management Network for Power Capping in Data Centers - Liu, Jie; Chandra, Ranveer (2013)
Data center management (DCM) is increasingly becoming a significant challenge for enterprises hosting large scale online and cloud services. Machines need to be continuously monitored, and the scale of operations mandate high reliability and automated management. Reliability in existing wired-based solutions for DCM comes with high cost. In this paper, we propose a new, wireless sensor-based approach that is significantly cost-effective while satisfying the reliability and performance requirements of management functions. Our system implementation, called CapNet, can scale to 100s of 1000s of servers at <10% the cost compared to wired implementation. We show its feasibility for a time critical DCM application – Power Capping – in a deployment of 80 machines in two different data centers, and also emulate implementation on 480 machines in an operational data center, using 6-month long power traces.